Problemas respiratórios e de claudicação em cavalos crioulos atletas - Abreu, Henrique Castagna de (2009)
This study was conducted to investigate two important causes of reduced performance in sport horses. In the first study, clinical records of 201 Criollo horses, 5.59±2.11 years of age, that underwent physical examination due to lameness or reduced performance in order to document the frequency of lameness problems in these horses. A total of 223 problems were diagnosed. In the forelimbs (47.08%; n=105) and in the hindlimbs (52.9%; n=118). In the forelimbs the pain was located above the fetlock joint in 17.14% (18/105), 14.30% (15/105) in the fetlock and 68.60% (72/105) distal to the fetlock. In the hindlimbs the source of lameness was frequently located in the hock (78.80%; 93/118). Lameness above the tarsus occurred in 17.80% (21/118) and below the tarsus in 3.4% (4/118) of the cases. This study showed that Criollo horses present similar lameness problems as seen in other breeds competing in rodeo disciplines. In the second study, 38 Criollo horses, 6.63±1.53 years of age, underwent endoscopic examination of the upper and lower airways, during competitions, aiming to document the frequency of respiratory problems and evaluate its impact on the Criollo horse s performance by their competition scores. Lymphoid hyperplasia was found in 57.89% (22/38) and left laryngeal hemiplegia (grade II) in 7.89% (3/38). Exercise induced pulmonary haemorrhage was diagnosed in 21.05% (8/38). Lower respiratory inflammation indicated by the presence of mucous or purulent secretion in the trachea was seen in 78.94% (30/38). There was no difference in the performance scores between horses diagnosed with EIPH and the ones considered normal (p>0.05). However, horses with mucous/purulent secretion in the trachea showed lower performance scores compared to the EIPH group (p=0.01). The high frequency of Criollo horses in this study showing inflammation in the lower respiratory tract indicates that endoscopic examination would help to identify horses with problems before the competitions.